AN INVESTIGATION INTO THE RELATED FACTORS OF INTELLECTUAL CAPITAL IN GOVERNMENTAL ORGANIZATIONS: A CASE STUDY OF THE GOVERNMENTAL ORGANIZATIONS IN KERMAN PROVINCE (IRAN) - Bafti, Azam; Salajegheh, Sanjar; Poorrashidi, Rostam (Revista Inclusiones, 2019)
Intellectual capital has an influential role in helping an organization to reach its purposes and many attentions have been paid to it in recent decades. The concept of intellectual capital is related to different factors, if studies, which can help the organizations to be prosperous. Hence, in the current study the related factors with the concept of intellectual capital are investigated with regard to the organizations of Kerman province (Iran). The participants of this study consisted two groups: the experts and the instructors of governmental management and the staff of executive organizations. To select the governmental management instructors all around Iran, 30 instructors who had the prerequisite criteria had been selected by using the opinions of their thesis supervisors. Moreover, using Morgan table 381 staff were selected to participate in this study. The data analysis by SPSS 22 and Liserl 22 showed that the factors such as capabilities and qualifications, technical knowledge, attitudes, culture, structure, organizational learning, technical capital, social services, social excellence, social connection, partner relationship, connection with the media, and the organization image of intellectual capital have positive effect on intellectual capital.